Exploring leadership style and employee attitude through cluster and sentiment analyses of in-depth interviews of employees - Dat Hung Ho; Jue Wang; Hak-Seon Kim (Administrative Sciences, 2023)
In today's fast-paced business environment, leaders who fail to recognize and respond to the emotions of their employees can result in stagnation or a lack of growth in their organization. In light of this, the current study presents a method for identifying leadership styles based on the perspectives of employees, exploring their perceptions of specific leadership traits. Drawing upon the Multifactor Leadership Questionnaire framework, this study aims to identify the leadership style of Tony Wedding Studio by conducting in-depth interviews with its employees. Through sentiment and cluster analyses of the collected data, the study identifies Idealized Influence Attributes and Laissez-faire as key leadership style traits. Additionally, this study sheds light on how employees react to and feel about their leader's leadership style, providing valuable insights for organizational development and leadership training. Overall, this study emphasizes the importance of understanding and responding to employee perspectives in effective leadership.
Keywords: 350; cluster analysis; employee attitude; in-depth interview; leadership style; sentiment analysis